2011
DOI: 10.1111/j.1365-2761.2011.01237.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel non‐motile phenotypes of Yersinia ruckeri suggest expansion of the current clonal complex theory

Abstract: The biochemical and cell surface characteristics of 63 non-motile isolates of Yersinia ruckeri from various sources were compared using the API 20E rapid identification system and conventional phenotypic methods. Eight individual phenotypic groups from a variety of fish species were observed from the data set. Non-motile isolates were not exclusively observed from serogroup O1; membership of biotype 2 was recorded for representatives from serogroups O2-O7. Variations in phenotypes highlights that new clonal gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 23 publications
1
18
1
1
Order By: Relevance
“…Both of the experimental fish pathogen (A. salmonicida and Y. ruckeri) were Gram negative when staining was performed using Gram staining method (Buck, 1982). Several studies have suggested that the A. salmonicida (Pedersen et al, 1994;Gudmundsdottir, 1998;Schmidt et al, 2000) and Y. ruckeri are gram negative fish bacteria (Tinsley et al, 2011;Verner-Jeffreys et al, 2011;Welch et al, 2011) which are reliable with the present results. The oxidase test was used to identify the presence of respiratory enzymes, cytochrome oxidase in the bacterial isolates.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Both of the experimental fish pathogen (A. salmonicida and Y. ruckeri) were Gram negative when staining was performed using Gram staining method (Buck, 1982). Several studies have suggested that the A. salmonicida (Pedersen et al, 1994;Gudmundsdottir, 1998;Schmidt et al, 2000) and Y. ruckeri are gram negative fish bacteria (Tinsley et al, 2011;Verner-Jeffreys et al, 2011;Welch et al, 2011) which are reliable with the present results. The oxidase test was used to identify the presence of respiratory enzymes, cytochrome oxidase in the bacterial isolates.…”
Section: Discussionsupporting
confidence: 85%
“…Non-motile Y. ruckeri, serovar type-I was described from rainbow trout (Oncorhynchus mykiss) in Spain (Fouz et al, 1990) and from hatchery-reared brown trout (Salmo trutta) in USA (Arias et al, 2007). The Y. ruckeri was also documented as non-motile, rod shaped phenotype from Europe and USA (Evenhuis et al, 2009;Tinsley et al, 2011;Verner-Jeffreys et al, 2011;Welch et al, 2011). Both of the experimental fish pathogen (A. salmonicida and Y. ruckeri) were Gram negative when staining was performed using Gram staining method (Buck, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…Serotyping is particularly important for strain differentiation of Y. ruckeri, and the O-serotyping scheme of Davies (14) is the most commonly used (12,(15)(16)(17). In this scheme, five O serotypes, O1, O2, O5, O6, and O7, are recognized by rapid slide agglutination assay using defined O antigens (14); the individual O serotypes correspond to discrete lipopolysaccharide (LPS) types as identified by SDS-PAGE and Western blotting (18).…”
mentioning
confidence: 99%
“…This approach allowed six distinct clonal groups to be distinguished among serotype O1 isolates and was able to differentiate between the classical Hagerman and the newly emerged biotype 2 strains (21). Subsequently, OMP analysis has played an important role in various epidemiological analyses of Y. ruckeri (9,15,24,(29)(30)(31).…”
mentioning
confidence: 99%
“…Stwierdzono, że szczepy należące do biotypu 2 są zdolne do przełamania odporności poszczepiennej, jeśli szczepionka była oparta na biotypie 1 (3,20). Uzyskane wyniki pokazały, że w opisywanym przypadku zarówno szczepy szczepionkowe, jak i te z przypadków chorobowych, nie wykazują ruchu, dlatego należą do biotypu 2.…”
Section: Wyniki I Omówienieunclassified